Survey of colourings and preservatives in drugs. Issue 6700 (9th September 1989) - Pollock, I.; Young, E.; Stoneham, M.; Slater, N.; Wilkinson, J. D.; Warner, J. O.
Abstract : OBJECTIVE–To assess the prevalence of colourings and preservatives in drug formulations in the United Kingdom. DESIGN–Postal survey. PARTICIPANTS–All pharmaceutical manufacturers in the United Kingdom were requested to supply data on drug formulations with particular regard to the content of colourings and preservatives. MAIN OUTCOME MEASURE–Prevalence in proprietary drugs of colourings or preservatives, or both, that have been implicated in adverse reactions. Computation of a list of formulations of bronchodilators, antihistamines, and antibiotics that are free of such additives. RESULTS–A total of 118 out of 120 pharmaceutical companies supplied the data requested. In all, 2204 drug formulations were analysed and found to contain 419 different additives, of which 52 were colourings and preservatives that have been implicated in adverse reactions; 930 formulations contained such an additive. Tartrazine was the fourth most commonly occurring colouring, being present in 124 drug formulations. CONCLUSION–Many drugs contain additives that help to identify them and prolong their shelf life but are implicated in adverse reactions in some people. Some form of labelling of drug additives would enable these people to avoid drugs containing such additives.